2017
DOI: 10.1080/21645515.2017.1386823
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous murine antimicrobial peptide CRAMP significantly exacerbates Ovalbumin-induced airway inflammation but ameliorates oxazolone-induced intestinal colitis in BALB/c mice

Abstract: Cathelicidin has been reported to be multifunctional. The current study aimed to investigate the influences of exogenous cathelicidin-related antimicrobial peptide (CRAMP) on inflammatory responses in different disease models. In OVA-induced allergic airway inflammation, CRAMP significantly enhanced the infiltration of inflammatory cells and accumulation of proinflammatory Th2 cytokine IL-13 and IL-33 in bronchial alveolar lavage fluid (BALF), exacerbated lung tissue inflammation and airway goblet cell hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Mast cell activation by LL-37 is thought to act through the MrgX2 receptor, a G protein-coupled receptor (GPCR), but other receptors, including FPRL1 and P2X7, have been proposed (88). The proinflammatory functions of cathelicidin have been observed in many human diseases and mouse inflammatory models (51,(89)(90)(91)(92), and this capacity to enhance tissue inflammation is consistent with the observations in our study. Interestingly, in the absence of cathelicidin, we saw an enhancement of neutrophil MPO release (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Mast cell activation by LL-37 is thought to act through the MrgX2 receptor, a G protein-coupled receptor (GPCR), but other receptors, including FPRL1 and P2X7, have been proposed (88). The proinflammatory functions of cathelicidin have been observed in many human diseases and mouse inflammatory models (51,(89)(90)(91)(92), and this capacity to enhance tissue inflammation is consistent with the observations in our study. Interestingly, in the absence of cathelicidin, we saw an enhancement of neutrophil MPO release (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The results of mouse experiments showed that porcine β-defensin 2 might improve mucosal lesions and extracellular permeability by targeting the NF-κB pathway and could thus alleviate inflammatory enteritis (Han et al, 2015). Cathelicidin-related antimicrobial peptide (CRAMP) restore body weight loss caused by ulcerative colitis and maintain colonic epithelial integrity (Li et al, 2018). Cathelicidin-BF can effectively inhibit the phosphorylation of NF-κB and increase the intestinal barrier function to reduce inflammation (Zhang H. et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As previously described [ 20 ], the first oocysts were found in the intestine 4 days post-inoculation (dpi) and the peak of infection was reached at 9 dpi. Surprisingly, whereas CRAMP expression is often described to be strongly upregulated under inflammatory conditions [ 18 , 22 , 23 ], it was significantly downregulated upon infection by C. parvum. The stronger mRNA downregulation was observed in the intestine at day 9 dpi ( Figure 1 C left panel).…”
Section: Resultsmentioning
confidence: 99%